Boosting Year 4 Science Education : A Dynamic Blend of Paper-Based and Computerized Board Games - Sim, Kah Ching; Mohd Kamal, Othman (UNIMAS Publisher, 2024)
This study examines using Paper-Based and Computerised Board Games with collaborative learning to enhance science learning involving 48 Year 4 participants from National-Type Chinese Primary Schools (24 Male and 24 Female). The study utilises a mixed-methods approach combining quantitative (pre-tests, post-tests, questionnaires) and qualitative (classroom observations, interviews) data to investigate the unique strengths of these pedagogical approaches. Paper-based Board Games with Collaborative Learning (CL) showed the most substantial impact on academic performance, motivation, and social interaction compared to Computerised Board Games with collaborative learning. The research suggests that paper-based board games might be a more effective tool for educators using CL to create engaging learning experiences in science for young students. Additionally, no significant difference between genders was observed in the learning scores. Further research with more extensive and diverse samples, longitudinal studies, and exploration in different contexts are recommended to broaden the understanding of these methods' effectiveness across various settings and learning goals